Impact of Frailty and Age on Clinical Outcomes in Patients Who Underwent Endovascular Therapy. (December 2022) - Nishikawa, Ken; Ebisawa, Soichiro; Miura, Takashi; Kato, Tamon; Yusuke, Kanzaki; Abe, Naoyuki; Yokota, Daisuke; Yanagisawa, Takashi; Senda, Keisuke; Wakabayashi, Tadamasa; Oyama, Yushi; Karube, Kenichi; et al.
Purpose: Information on the relationship between frailty and the outcome of endovascular therapy (EVT) in elderly patients with lower extremity peripheral artery disease (PAD) is scarce. This study aimed to reveal the impact of frailty on the prognosis of super-elderly patients who underwent EVT. Materials and Methods: From August 2015 to August 2016, 335 consecutive patients who underwent EVT were enrolled in the I-PAD registry from 7 institutes in Nagano prefecture. Among them, we categorized 323 patients into 4 groups according to age and the presence or absence of frailty as follows: elderly with frailty (age ≥ 75, Clinical Frailty Scale [CFS] ≥ 5), elderly without frailty (age ≥ 75, CFS ≤ 4), young with frailty (age < 75, CFS ≥ 5), and young without frailty (age < 75, CFS ≤ 4); we analyzed them accordingly. The primary endpoints were major adverse cardiovascular and limb events (MACLE), defined as a composite of cardiovascular death, myocardial infarction, stroke, admission for heart failure, major amputation, and revascularization. The secondary endpoint was cardiovascular death. Results: The median follow-up period was 2.7 years. In the elderly with frailty, elderly without frailty, young with frailty, and young without frailty groups, the freedom rates from MACLE were 34.9%, 55.7%, 35.4%, and 63.0%, respectively (p<0.001) and from all-cause death were 43.5%, 73.4%, 50.7%, and 90.9%, respectively (p<0.001). The freedom rates from MACLE were significantly higher among elderly patients with frailty than among young patients without frailty (55.7% vs 35.4%, p=0.01). In multivariate analysis, frailty was independently associated with MACLE incidence. Conclusion: Frailty as defined by CFS might be a predictor of MACLE incidence in patients with PAD who underwent EVT. By considering treatment indications for patients with PAD by focusing on frailty rather than age, we may examine whether EVT policies are appropriate and manage patient and caregiver expectations for potential improvement in functional outcomes. Further studies are expected to investigate whether changes in frailty after EVT change prognosis.